Spinal Cord Stroke: Acute Imaging and Intervention - Karen Lynch; Joel Oster; Diana Apetauerova; Kinan Hreib (Case Reports in Neurological Medicine)
Spinal cord infarction is an uncommon disease and as such is often a diagnostic challenge for clinicians. It can vary in its onset, severity, outcome, and recovery from patient to patient. Treatment options for this relatively rare condition also remain elusive. Current consensus recommendations are antiplatelet therapy and the symptomatic management of associated complications such as paraplegia and thromboembolic disease. There are multiple studies in surgical literature of a variety of interventions and adjuncts used for reducing the risk of ischemic spinal cord neurological injury, seen most often in the setting of thoracoabdominal aortic repair operations. We report two cases of acute non-surgical-related spinal cord infarcts, where early diagnosis was made and aggressive, early treatments instituted. With often devastating outcomes, we highlight the need for early detection and that interventions, commonly used in preventing neurological injury after high-risk aneurysm repairs, may be beneficial in treating and reducing the severity of disability in acute spinal cord stroke.